INTEGRATION OF SCIENCE AND RELIGION IN ISLAMIC RELIGIOUS EDUCATION - Abdul Latif Harahap; Rahmawati Nasution (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2024)
Islamic Religious Education (PAI) plays a strategic role in developing a generation that is not only intellectually intelligent but also possesses faith and noble morals. One relevant approach is the integration of science and religion, which aims to align spiritual values ​​with scientific advancement. This integration is based on the concept of monotheism as a foundation, which affirms that there is no contradiction between God's revelation and true science. In the context of PAI, this integration can be realized through the study of Quranic verses relevant to scientific phenomena, the teaching of scientific ethics based on Islamic values, and a contextual learning approach. With this approach, students are expected not only to understand Islamic teachings in depth but also to be able to apply them in social life. However, this integration faces various challenges, such as curriculum gaps and limited competency of educators. Therefore, synergy is needed between educational institutions, educators, and educational policies to realize a holistic education.